2020
DOI: 10.1158/1078-0432.ccr-20-1301
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I/II Study of Veliparib (ABT-888) in Combination with 5-Fluorouracil and Oxaliplatin in Patients with Metastatic Pancreatic Cancer

Abstract: Purpose: Up to 17% of patients with pancreatic ductal adenocarcinoma (PDAC) harbor pathogenic (germline or somatic) mutations in a homologous recombination, DNA damage response and repair (HR-DDR) gene, such as BRCA1/2, or PALB2. Platinum-based chemotherapy, or treatment with PARP inhibitors are of particular benefit in these patients. However, there may be even greater benefit when platinums and PARP inhibitors are combined.Patients and Methods: We performed a single-arm, open-label, phase I/II study of the P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…A recently published phase 1 to 2 study of veliparib plus modified FOLFOX‐6 in patients with pancreatic cancer ( n = 64) established the RP2D at veliparib 200 mg twice daily plus oxaliplatin 85 mg/m 2 and 5‐FU 2400 mg/m 2 continuous infusion over 46 hours 70 . Again, the 5‐FU bolus was omitted due to prolonged myelotoxicity among the first treated patients, and additional dose reductions of at least one component were necessary in all patients.…”
Section: Completed Clinical Studiesmentioning
confidence: 99%
“…A recently published phase 1 to 2 study of veliparib plus modified FOLFOX‐6 in patients with pancreatic cancer ( n = 64) established the RP2D at veliparib 200 mg twice daily plus oxaliplatin 85 mg/m 2 and 5‐FU 2400 mg/m 2 continuous infusion over 46 hours 70 . Again, the 5‐FU bolus was omitted due to prolonged myelotoxicity among the first treated patients, and additional dose reductions of at least one component were necessary in all patients.…”
Section: Completed Clinical Studiesmentioning
confidence: 99%
“…Lynch syndrome from mismatch repair (MMR) gene mutations, Peutz-Jeghers syndrome from STK11 mutations) [9]. Moreover, our knowledge about other cancers (e.g., ovary, prostate) underscores the possible therapeutic implications of a broader range of DDR gene mutations [15][16][17][18][19][20], and this concept has recently been extended to PC [40,41]. This highlights the need for genetic screening beyond BRCA: in our opinion it is mandatory to take advantage of a gene panel that cannot exclude essential genes such as ATM, PALB2, RAD50, STK11 and MMR genes [9,31,40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in cancers other than PC (i.e. ovarian and prostate) have shown that BRCA1 and BRCA2 are not the only genes whose alteration is essential in this context: indeed, the wider concept of HR deficiency, including other genes such as ATM or PALB2, is implicated in the exploitation of synthetic lethality [15][16][17][18][19][20]. Furthermore, new treatment options that take advantage of this mechanism are emerging in addition to PARPi.…”
Section: Introductionmentioning
confidence: 99%
“…A phase I/II trial of veliparib with FOLFOX (5-FU, oxaliplatin, folinic acid) has demonstrated an acceptable safety profile. The primary endpoint ORR at 26% was met, while the ORR was even higher at 30-58% for patients with a family history suggestive of breast and ovarian cancer syndrome or DDR mutation [170]. This warrants further investigation with a randomized double-arm clinical trial to validate a benefit of adding veliparib to FOLFOX.…”
Section: Pancreatic Cancermentioning
confidence: 91%